1281 ANALYSIS RUBRICS CONSTRUCTION OF SCIENCE CONTENT THEMATIC BOOKS GRADE VI - WIONO, WISNU JULI
Rubric is an integral part of the assessment. The advantage of using the rubric of teachers more focused in giving reciprocity to student learning outcomes. Principal component within the rubric are the criteria and levels of achievement. Both components must be written in language that is operational and free ambiguous. The criteria should be limited in number to efficient use. Still found a section with a lot number of criteria and operational bias in sixth grade teacher books , especially science payload. Rubric integrated with Indonesian charge less to accommodate the ability of science. The necessary simplification of the construction section in the book. Simplification was related to the teacher as a user maind set.